Chemically modified lipase from Thermomyces lanuginosus with enhanced esterification and transesterification activities - Noro, Jennifer Martins (2021)
Lipase from Thermomyces lanuginosus is one of the most explored enzymes for the esterification of several added-value industrial compounds, such as biodiesel, fragrances, and flavors. Its selectivity in these reactions is mostly related with its activity towards small alcohols. In this work, the impact of the chemical modification, with 4 dodecyl chains at its surface, was evaluated regarding its transesterification and esterification activities, comparing with the native form. Linear size-differentiated alcohols (from 1 to 20 carbons in the aliphatic chain) were used to explore for the first time the effect of the chain length in both transesterification and esterification reactions, using p-nitrophenyl palmitate and oleic acid as model compounds, respectively. The chemically modified lipase showed an outstanding improvement of its catalytic performance than the native enzyme, being this increase directly proportional to the size of the alcohols chain used as substrates. The enormous potential and remarkable versatility of this novel super catalyst was here demonstrated, where diverse types of esters, differing in their potential applications (biodiesel, cosmetics, fine chemistry), were efficiently synthesized. The produced esters were fully characterized by 1H NMR, GC-MS, and FTIR.